Emergomycosis (Emergomyces africanus) in Advanced HIV Disease - Nelesh P. Govender; Wayne Grayson (Dermatopathology, 2019)
In 2013, a novel thermally dimorphic fungal pathogen was described to cause disseminated disease among persons living with advanced HIV/AIDS in South Africa. Although the organism was initially described as an Emmonsia-like fungus, it is now known to belong to a new genus of thermally dimorphic fungi and was recently named Emergomyces africanus. There is considerable clinical and histopathological overlap between emergomycosis and histoplasmosis. This review addresses taxonomic, clinical, diagnostic, and therapeutic aspects of Es. africanus disease, a condition which has, to date, only been reported from southern Africa.